2015
DOI: 10.3126/jmmihs.v1i4.11996
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Standing and Supine Lateral Radiographs in Low Grade Spondylolisthesis

Abstract: To analyze the differences between standing and supine plain film lateral radiographs of the lumbosacral region in low grade (grade I/II) spondylolisthesis using the Picture Archiving and Communication System (PACS) software. Demonstrable difference might be a parameter of instability which might be useful in planning surgical treatment when it is too painful for patients to undergo flexion/extension Xrays.Radiographs of 23 patients with low grade spondylolisthesis were analyzed for percentage slip, lumbar lor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Pelvis inclination ranged from À21 to 5 in the supine and standing positions, respectively, and there was a strong correlation between the two positions (R ¼ 0.88). Another study [34] was conducted to evaluate the differences between the two positions using lateral x-ray images. Twenty-three patients were imaged and the results showed no significant differences in lumbar lordosis (P ¼ .06), sacral inclination (P ¼ 1.00).…”
Section: Pelvic Sagittal Inclination To Evaluate Ptmentioning
confidence: 99%
See 2 more Smart Citations
“…Pelvis inclination ranged from À21 to 5 in the supine and standing positions, respectively, and there was a strong correlation between the two positions (R ¼ 0.88). Another study [34] was conducted to evaluate the differences between the two positions using lateral x-ray images. Twenty-three patients were imaged and the results showed no significant differences in lumbar lordosis (P ¼ .06), sacral inclination (P ¼ 1.00).…”
Section: Pelvic Sagittal Inclination To Evaluate Ptmentioning
confidence: 99%
“…It should be noted that a number of studies [27][28][29][30]34,44] have reported on the use of lateral pelvis images and their utility in the management of hip pathologies. The purpose of our review was to compare likely variations between erect and supine AP pelvic imaging and not to evaluate the utility of a lateral projection.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…These are then used to measure sagittal plane intervertebral motion. A myriad of patient positioning protocols have been tested or deployed (11,58,70,(97)(98)(99)(100)(101)(102)(103)(104)(105) extension with a mechanically controlled device provokes more translation than the "standard of care" exionextension they analyzed. The list goes on, and the research continues while the "standard of care" remains unstandardized.…”
Section: Flexion-extensionmentioning
confidence: 99%
“…Several studies have suggested that recumbent radiographs are inferior to standing films for lumbar spondylolisthesis, with a significant difference in percentage slip between standing and supine imaging. 15,16 Furthermore, a study by Gardner et al 17 demonstrated that supine MRI often underestimates the extent of rotary subluxation. The author's suggestion that it is beneficial to include long spine or full-body AP radiographs as a standard component of preoperative imaging for deformity patients is therefore a good one and may be critical to operative planning.…”
mentioning
confidence: 99%